1982
DOI: 10.1182/blood.v60.1.130.130
|View full text |Cite
|
Sign up to set email alerts
|

In vitro proliferation of hematopoietic stem cells in the absence of an adherent monolayer

Abstract: Experiments on long-term murine bone marrow cultures indicate that the production and maintenance of the hematopoietic stem cell is dependent on the establishment of an adherent monolayer and a secondary repopulation of the culture with fresh marrow. In contrast, we have found that bone marrow cultures derived from the Syrian hamster do not require a repopulation step and produce stem cells that proliferate and differentiate for more than 12 wk in the absence of an adherent layer. Stem cells were grown in Fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Based on the well‐established ability of BM‐MSC to support hematopoietic cell growth via cytokine secretion (Eastment, Denholm, Katsnelson, & Arnold, ), BM‐A and BM‐MSC culture supernatants were examined for cytokines that might positively or negatively affect HSC support.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the well‐established ability of BM‐MSC to support hematopoietic cell growth via cytokine secretion (Eastment, Denholm, Katsnelson, & Arnold, ), BM‐A and BM‐MSC culture supernatants were examined for cytokines that might positively or negatively affect HSC support.…”
Section: Resultsmentioning
confidence: 99%
“…Since cell‐cell signaling is vital for HSC maintenance and activation (Eastment et al, ; Eaves & Eaves, ), five key pathways involved in the process were examined: activation of blood cells, leukocytes, phagocytes, myeloid cells, and antigen‐presenting cells. The five pathways exhibited differential regulation, and the cluster analysis findings obtained from array expression data demonstrated that BM‐A were closer to BM‐MSC than to AT‐A (Supplementary Figure S5A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations